The Amazing World of Gumball: Recipe for Disaster - Bocquelet, Ben; Brennan, Megan; Sherron, Kate; Farina, Katy; Brennan, Megan; Sherron, Kate. (Los Angeles, CA KaBoom!, [2017], 2017)
Gumball and Anais are forced to choose between letting Mr.Dad and Darwin follow their dream of entering the Annual Elmore Bake-off or save the world, after future Gumball warns them of the reprecussions of the current bake-off champion losing.
Chiefly illustrations.
Keywords: Baking -- Juvenile fiction; Time travel -- Juvenile fiction; Cats -- Fiction; Rabbits -- Fiction; Family life -- Fiction; Cats -- Cartoons and comics; Rabbits -- Cartoons and comics; Family life -- Cartoons and comics; Graphic novels